Efficacy of combined virtual reality with constraint-induced movement therapy on upper limb function of children with hemiparetic cerebral palsy - Hamid Reza Rostami; Ali Asghar Arastoo; Seifollah Jahantabi Nejad; Reza Azizi Malamiri; Mohammad Khayatzadeh Mahany; Shahin Goharpey (Vesnu Publications, 2012)
Introduction: Hemiparetic cerebral palsy refers to an impairment caused by non-progressive damages to premature brain which is more sever in one side of the body than the other side. The aim of the present study was to determine the effects of combining constraint-induced movement therapy (CIMT) with virtual reality (VR) on upper limb functioning of children with hemiparetic cerebral palsy. Materials and Methods: In a single blind randomized, controlled trial, 16 children with hemiparetic cerebral palsy, who were selected through a simple random sampling method in Ahvaz city, were divided into 4 groups of CIMT, VR, CIMT+VR, and controls. Subjects in experimental groups participated in one-and-half-hour therapeutic sessions which were held every other day during a four-week period. Measures were conducted pre, post and 3-month after the treatment period using Pediatrics Motor Activity Log and Bruininks-Oseretsky Test of Motor proficiency (BOTMP). Sample randomization and statistical analysis of data through analysis of variance with repeated measures were conducted via SPSS-16 software in which alpha level was set at 0.05. Results: Data analysis for measurement tools was indicative of significant difference of combined group compared to VR, CIMT, and control groups (P < 0.01) (mean amounts of BOTMP, speed and dexterity changed from 0.15 ± 0.08 to 1.89 ± 0.33 in post-test). Data analysis for follow-up session revealed the retention of results for 4 groups (P = 0.32). Conclusion: Incorporating VR and CIMT may improve upper limb functioning of children with hemiparetic cerebral palsy through combining the advantages of both protocols and implementing them in an integrated program. Keywords: Constraint-induced movement therapy, Virtual reality, Upper limb function, Hemiparetic cerebral palsy